2020
DOI: 10.1155/2020/7292675
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Strategies for Preventing Contrast-Induced Acute Kidney Injury: A Systematic Review and Bayesian Network Meta-Analysis

Abstract: Aims. Many previous studies have examined the effect of different hydration strategies on prevention of contrast-induced acute kidney injury (CI-AKI), but the optimal strategy is unknown. We performed a network meta-analysis (NWM) of these previous studies to identify the optimal strategy. Methods and Results. Web of Science, PubMed, OVID Medline, and Cochrane Library were searched from their inception dates to September 30, 2018. Randomized controlled trials (RCTs) were selected based on strict inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 87 publications
0
7
0
2
Order By: Relevance
“…Cai et al reviewed hydration strategies in 60 RCTs and performed a network meta-analysis to find an optimal strategy [ 124 ]. They reported that the RenalGuard system was best, followed by hemodynamic guidance monitoring for hydration.…”
Section: Managementmentioning
confidence: 99%
“…Cai et al reviewed hydration strategies in 60 RCTs and performed a network meta-analysis to find an optimal strategy [ 124 ]. They reported that the RenalGuard system was best, followed by hemodynamic guidance monitoring for hydration.…”
Section: Managementmentioning
confidence: 99%
“…Although the effectiveness of hydration therapy has been well recognized, the agents, timing, dose, and velocity of optimal hydration strategy remain inconclusive 36 38 . Debates mainly focused on the choice of intravenous normal saline infusion or intravenous sodium bicarbonate infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al . [30] performed a meta-analysis of 60 PRCTs evaluating various fluid administration strategies for CA-AKI in 21 293 patients. Oral hydration and isotonic (0.9%) saline (IS) were each noninferior to no fluid administration in preventing CA-AKI and that when oral hydration was the reference, IS and NB were noninferior in prevention of CA-AKI.…”
Section: Fluid Administation Versus No Fluid Administationmentioning
confidence: 99%